Coping skills of Olympic developmental soccer athletes - Meyers, M. C.; Stewart, C. C.; Laurent, C. M.; LeUnes, A. D.; Bourgeois, A. E. (International Journal of Sports Medicine, 2008)
Athletes at Olympic Developmental Program (ODP) camps experience unusually high levels of expectations and inherent mental and physical challenges within such a short span of time. With the increasing emphasis on talent development, there has been consensus by the ODP staff to more clearly define present levels of coping skills, in order to enhance athletic prediction, maximize training efforts, identify the predisposition to injury, and focus on areas pertinent to successful performance. This study examined athletic and pain coping skills of U. S. ODP soccer athletes not previously investigated. Following written informed consent, 70 males completed the Athletic Coping Skills Inventory and the Sports Inventory for Pain. Data were analyzed by competitive level (U-14, U-15), and skill position (goalkeeper/defense, midfield/foward). MANOVA indicated a significant main effect across competitive level (Wilks' Lambda F12,57 = 2.27; p = 0.02; n-ß = 0.915) but no significant effect by skill position (Wilks' Lambda F12,57 = 0.931; p = 0.523; n-ß = 0.457). Post hoc analyses indicated that U-15 athletes scored significantly higher in concentration (p = 0.01) and body awareness (p = 0.03), but lower in avoidance (p = 0.01) than U-14 competitors. In conclusion, older, more experienced athletes revealed more positive athletic and pain coping skills than younger, less experienced athletes, although athletes in skill positions requiring spontaneous decision-making skills and split-second adjustment in a constantly changing sport environment (forwards, midfielders) did not exhibit more positive athletic and pain coping skills than those positions requiring reaction and protection (defenders, goalkeepers).